2013
DOI: 10.3941/jrcr.v7i3.1336
|View full text |Cite
|
Sign up to set email alerts
|

Malignant fat-forming solitary fibrous tumor (lipomatous hemangiopericytoma) in the neck: Imaging and histopathological findings of a case

Abstract: Fat-forming solitary fibrous tumor (SFT) is a rare variant of solitary fibrous tumor, a mesenchymal fibroblastic neoplasia with a particular branching hypervascular pattern. This tumor is usually classified as benign and only very few fat-forming SFTs with malignant histologic features have been reported. We report a histologically malignant fat-forming solitary fibrous tumor in a 61-year-old man, located in his neck. Ultrasonography examination was first performed showing a heterogeneous lesion, predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Fat-forming SFTs usually occur in older adults, predominantly in males, and have a broad anatomical distribution 1. Although fat-forming SFTs are typically nonrecurring and nonmetastasizing benign tumors, they can show malignant histologic features and malignant behavior 2-5. Reported cases of malignant fat-forming SFTs revealed that men and women are equally affected, that the age of patients ranged from 20 to 93 years, and that the maximal size of a malignant tumor was 20 cm (range, 3.4 to 20 cm).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fat-forming SFTs usually occur in older adults, predominantly in males, and have a broad anatomical distribution 1. Although fat-forming SFTs are typically nonrecurring and nonmetastasizing benign tumors, they can show malignant histologic features and malignant behavior 2-5. Reported cases of malignant fat-forming SFTs revealed that men and women are equally affected, that the age of patients ranged from 20 to 93 years, and that the maximal size of a malignant tumor was 20 cm (range, 3.4 to 20 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Reported cases of malignant fat-forming SFTs revealed that men and women are equally affected, that the age of patients ranged from 20 to 93 years, and that the maximal size of a malignant tumor was 20 cm (range, 3.4 to 20 cm). These tumors commonly involve the thigh and could also affect variable anatomical sites including the calf, neck, scalp, posterior thoracic cavity, ligamentum teres of the liver, arm, pelvis, lower back, vulva, and retroperitoneum 2-5. All of the reported malignant fat-forming SFTs were well emarcated and encapsulated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations